2014
DOI: 10.1155/2014/412105
|View full text |Cite
|
Sign up to set email alerts
|

Screening Donated Blood for Transfusion Transmitted Infections by Serology along with NAT and Response Rate to Notification of Reactive Results: An Indian Experience

Abstract: Background. Transfusion safety begins with healthy donors. A fundamental part of preventing transfusion transmitted infections (TTIs) is to notify and counsel reactive donors. Donor notification and counselling protect the health of the donor and prevent secondary transmission of infectious diseases. Methods. 113,014 donations were screened for TTIs, namely, HIV, HBV, HCV, and syphilis, by serology and nucleic acid testing. All reactive donors were retested (wherever possible) and notified of their status by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 22 publications
4
28
4
Order By: Relevance
“…The NAT yield rate of one in 847 is higher than the first study result (one in 2622) reported by Chatterjee et al at our centre [14]. Agarwal et al and Chaurasia et al have reported a higher NAT yield of one in 610 and one in 628, respectively [12,13]. These variabilities in NAT yield rates could be attributed to much larger sample size taken into account in the current study.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The NAT yield rate of one in 847 is higher than the first study result (one in 2622) reported by Chatterjee et al at our centre [14]. Agarwal et al and Chaurasia et al have reported a higher NAT yield of one in 610 and one in 628, respectively [12,13]. These variabilities in NAT yield rates could be attributed to much larger sample size taken into account in the current study.…”
Section: Discussioncontrasting
confidence: 65%
“…and Chaurasia et al . have reported a higher NAT yield of one in 610 and one in 628, respectively . These variabilities in NAT yield rates could be attributed to much larger sample size taken into account in the current study.…”
Section: Discussionmentioning
confidence: 54%
“…For example, transmission through blood transfusion despite the high odds, but in fact such cases are very rare, because of transmission through blood transfusion can be controlled through the process of screening blood donors beforehand calor (John, 2011). If found blood containing the HIV virus during the screening process, then the blood will not be used for blood transfusions (Chaurasia et al, 2014;Shitu et al, 2014). Instead, transmission through the razor is still a serious concern for everyone.…”
Section: Correlation Between Knowledge and The Risk Of Hiv Transmissimentioning
confidence: 99%
“…[1234] Majority of the blood banks in India are using ELISA-based serologic screening for transfusion-transmissible viral infections (TTIs). The automated platform for chemiluminescence (ACLS) has been introduced in the recent past, as a newer serological screening tool that offers good precision, reliability, and high throughput.…”
mentioning
confidence: 99%